ANALISIS PENGARUH MINAT PELAJAR DAN MAHASISWA BERWIRAUSAHA SESUAI DENGAN PRINSIP-PRINSIP EKONOMI DAN BISNIS ISLAM DI MASA PANDEMI COVID-19 - Muhamad Ismail; Tubagus Rifqy Thantawi; Bayu Purnama Putra (Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2022)
The Covid-19 pandemic has resulted in an economic downturn that has impacted workers so that many are unemployed. One of the efforts that can be done to reduce unemployment is to encourage the creation of new entrepreneurs. As young people who are the successors of the nation, students and students can be a driving force in forming entrepreneurship. Students and students can start entrepreneurship by studying entrepreneurship. In entrepreneurship, the attitude and behavior of a strong entrepreneur is implanted. However, it is necessary to examine the factors that motivate students' interest in entrepreneurship, especially in accordance with Islamic economic and business principles. This study aims to determine the influence of the factors of Interest in Entrepreneurship, Family Environment, School Environment, Government Support on Student Interest and Entrepreneurship in accordance with Islamic Economics and Business Principles during the Covid-19 pandemic. The population in this study were students and college students, with a sample of 82 people. The method used is an interview using a questionnaire. The analysis tool uses multiple linear regression analysis. The results of hypothesis testing indicate that Interest in Entrepreneurship, Family Environment, School Environment, and Government Support have an effect on Student Interest and Entrepreneurship in accordance with Islamic Economics and Business Principles during the Covid-19 pandemic.